Reading the whole page teaching and assessing text features to meet K-5 common core standards - Kelley, Michelle; Nicki (Gainesville, FL Maupin House, 2012)
When K-5 students understand how to read text features like bullets, insets, and bold print, they are reading the whole page essential for deep comprehension of non-fiction and fiction text. In Reading the Whole Page: Teaching and Assessing Text Features to Meet K-5 Common Core Standards, seasoned educators Michelle Kelley and Nicki Clausen-Grace show you how to explicitly teach K-5 students to read text features
A gift from book Africa
English Languges
1 2 13 15
NEW_ZTN_GN
Keywords: Reading (Elementary) -- Standards -- United States; Reading (Elementary) -- Ability testing -- United States